Design Professional Rice Business in Tabanan Regency - I Gusti Bagus Udayana; Gede Sedana; I Ketut Sunadra (Warmadewa University Press, 2018)
Rice is the main food ingredient of the people of Indonesia. Rice is used primarily to be processed into rice, and a variety of other foods. Every day, households need rice for consumption. This is what makes the velocity of money in the business of rice is very fast. Rice itself has various types and levels of quality. Every kind of rice certainly has a different price. Thus, each consumer determines the kind of rice to be consumed. In Tabanan regency, agriculture is a very potential field, so it is included in the category of excellent potentials, especially food crops such as rice. Since 2013, the Government of Tabanan Regency has planned agricultural programs that implement organic farming systems on paddy fields. Everyone needs rice because this product is the staple food of the people, especially Indonesian citizens from the start of small children, adolescents, until the parents need rice as the main ingredient of him every day. Therefore the tremendous business opportunity of selling rice will never end. The resulting product is called